The Thurwieser rock avalanche (Italian Alps): description and dynamic analysis - PIRULLI, MARINA (Engineering Geology, 2009)
A rock avalanche of about 3•10^6 m3 detached from the South-East flank of the Punta Thurwieser ridge (Italian Central Alps) on the 18th of September, 2004. Due to the characteristics of the moving material (i.e. rock, debris, ice, snow) and the path of propagation (e.g. presence of a glacier), the mass was able to rapidly cover long distances (about 3000 m). Among the possible causes of the event, attention is mainly focused on permafrost degradation and changes in glacier extension due to global warming. In the present work, the dynamics of the event and the role played by characteristics of the propagation path are numerically investigated with the RASH3D code, based on a continuum mechanics approach. Results obtained with two rheological hypotheses (Frictional and Voellmy) are compared and discussed. In particular, it emerges that 1) the use of a Voellmy rheology with a reduced friction angle on the glacier is necessary to reproduce the dynamics of the Thurwieser event, and 2) a lack in knowledge of geometrical and geomechanical information may lead to wrong interpretations of the event and inaccurate calibration of numerical models.